IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR SDN 13 BATANG GASAN KAB. PADANG PARIAMAN - Ahmad Zikri; Nurhizrah Gitituati; Alwen Bentri (LPPM Universitas Ekasakti, 2024)
The curriculum has a central role in the world of education, serving as a guideline for designing and implementing the learning process. guidelines for designing and implementing the learning process. This paper illustrates the importance of curriculum in directing education, as well as improve the quality of learning. With a focus on the curriculum of SD Negeri 13 Batang Gasan, which is located in Batang Gasan, Padang Pariaman Regency, the diversity of students and the environment is an important factor in the development of education services. educational services. Diversity is considered an asset and a challenge that motivates the school to realize its vision with a commitment to guide students with compassion. This curriculum emphasizes active learning, creative, effective and fun, utilizing existing facilities and potential. The values of national culture and character, such as religion, honesty and tolerance, are integrated into all educational activities as part of the school's vision, are integrated in all educational activities as part of the school culture. Through the curriculum, SD Negeri 13 Batang Gasan is committed to implementing educational programs according to the characteristics, potential and needs of students. The curriculum development process involves the entire school community in coordination with stakeholders around the school. This means that the curriculum is not only a formal tool, but also the main foundation in achieving the goals of quality education and the main foundation in achieving the goals of quality education and adaptive to the needs of learners, adaptive to the needs of students.